STUDI HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS (HKSA) DAN DOCKING MOLEKULER SENYAWA TURUNAN OXABICYCLOHEPTENE SULFONAMIDE (OBHS) SEBAGAI ANTAGONIS RESEPTOR ESTROGEN- α PADA TERAPI KANKER LEHER RAHIM (SERVIKS) - Nursalam Hamzah; Afrisusnawati Rauf; Asyraful Anam (Jurnal Farmasi UIN Alauddin Makassar, 2014)
A research study of quantitative structure-activity relationship (QSAR) and molecular docking of Oxabicycloheptene Sulfonamide (OBHS) derivates as Estrogen Receptor α (ERα) antagonist in Cervical Cancer treatment was performed. This study aims to find similarities QSAR models of Oxabicycloheptene Sulfonamide derivates as ERα antagonist and assess the interaction model of Oxabicycloheptene Sulfonamide derivates towards the side of the ERα (pdb code:   1G50   and   3ERT)   binding   (binding   site).   In   this   research   tested   against   9 Oxabicycloheptene Sulfonamide derivate compounds. The first, drawing compounds and ab initio optimization at the HyperChem program. Further test descriptor values, statistical calculation method multilinier regression analysis, z-score validation and Leave-One-Out validation method. Obtained from experiments performed equation : log 1/IC50 = 5.2006 + (- 3.52E-06 AM1_Eele) + (4.46E-05 AM1_HF) + (0.5737 log S) + (0.8919 mr) + (-0.0392 vol), which n = 9, r2 = 0.9404, and q2 = 0.7388. In the process of molecular docking, ligand and receptor preparation done first before to performing docking simulation. Obtained results from docking to protein code 1G50 experiments which compound 13 showed better results with a docking score (S) -12.2016. Then, results from docking to protein code 3ERT experiments which compound 12 showed better results with a docking score (S) -10.3484.